Extraction and purification of S-adenosyl-L-methionine from Saccharomyces cerevisiae IFO 2346 - Hường Trần Thị; Hồng Phạm Thúy; Trâm Nguyễn Thị Hoài; Hải Trương Nam (Vietnam Journal of Biotechnology, 2008)
Journal of Biotechnology 3(1): 115-121, 2005